2021
DOI: 10.3389/fimmu.2020.592328
|View full text |Cite
|
Sign up to set email alerts
|

Improved Functionality of Exhausted Intrahepatic CXCR5+ CD8+ T Cells Contributes to Chronic Antigen Clearance Upon Immunomodulation

Abstract: Chronic hepatotropic viral infections are characterized by exhausted CD8+ T cells in the presence of cognate antigen in the liver. The impairment of T cell response limits the control of chronic hepatotropic viruses. Immune-modulatory strategies are attractive options to re-invigorate exhausted T cells. However, in hepatotropic viral infections, the knowledge about immune-modulatory effects on the in-situ regulation of exhausted intrahepatic CD8+ T cells is limited. In this study, we elucidated the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Suppression of viral replication in the liver correlated with the intrahepatic expression of type I and II IFNs [42]. The importance of the TLR9 signaling as a new target for stimulatory approaches was also emphasized by a recent report demonstrating that host conditioning with the CpG oligonucleotide could restore exhausted intrahepatic CXCR5+ CD8 T cells, via upregulation of co-stimulatory molecules CD80/86 and OX40 on myeloid cells with subsequent increase of CD28-mediated signals on T cells [72].…”
Section: Stimulation Of Innate Immunity Receptors As An Immunomodulatory Strategy To Overcome Hbv-specific T Cell Exhaustionmentioning
confidence: 99%
“…Suppression of viral replication in the liver correlated with the intrahepatic expression of type I and II IFNs [42]. The importance of the TLR9 signaling as a new target for stimulatory approaches was also emphasized by a recent report demonstrating that host conditioning with the CpG oligonucleotide could restore exhausted intrahepatic CXCR5+ CD8 T cells, via upregulation of co-stimulatory molecules CD80/86 and OX40 on myeloid cells with subsequent increase of CD28-mediated signals on T cells [72].…”
Section: Stimulation Of Innate Immunity Receptors As An Immunomodulatory Strategy To Overcome Hbv-specific T Cell Exhaustionmentioning
confidence: 99%
“…CXCR5 + CD8 T cells have special phenotypes: for example, 1) cell markers including CD11a, CD11b, CD20, CD25, CD27, CD28, CD38, CD39, CD40, CD43, CD44hi, CD45RA, CD45RO, CD57, CD62L, CD69, CD83, CD94, CD95, CD101, CD103, CXCR5,CD107, CD127, CD137, CD161, CD200, CD244, HLA-DR, 41BBL, Slamf6, and TCRVa7.2 [ 13 , 131 , 145 , 146 , 149 , 151 155 , 157 160 , 163 165 , 167 , 168 , 171 , 174 , 176 178 , 180 182 , 184 190 , 193 195 , 197 , 199 , 201 , 204 , 205 , 207 , 211 , 212 , 214 ]; 2) cytokines, chemokines and receptors (CSF-1, IL-2, IL-4, IL-6, IL-7, IL-7R, IL-10, IL-17, IL-18Ra, IL-21, IL-21R, IL-22, IL-23, IL-27, IL-27R, IL-35, IFN-I, IFNAR1, IFN-γ, TGF-β, TNF-α, IL-4R (CD124), CCR2, CCR4, CCR5, CCR6, CCR7, CCR9, CCL5, CXCL1, CXCL5, CXCL10, CXCL12 (SDF-1α), CXCL13, CXCR3, CXCR4, CXCR5, CX3CR1, MIP-1β) [ 144 146 , 149 , 151 , 153 , 154 , 157 , 159 162 , 165 , 167 , 168 , 170 , 172 174 , 176 , 177 , 179 , 181 186 , 188 , 190 , 191 , 193 197 , 199 , 200 , 205 , 206 , …”
Section: Cxcr5 + Cd8 + T Cells ...mentioning
confidence: 99%
“…Recently, a novel subset of CD8 T cells, CXCR5 + CD8 + T cells, were identified [141][142][143]. CXCR5 + CD8 + T cells have been found to infiltrate the B cell follicle in response to several diseases, including viral infection (simian immunodeficiency virus (SIV) or human immunodeficiency virus (HIV) , lymphocytic choriomeningitis virus (LCMV) [149,171,172], hepatitis B virus (HBV) [173][174][175][176][177][178][179][180], polycythemia-inducing FV [180], FluA [181,182], HSV [183], DENV2 [184,185], and SARS CoV-2 [186][187][188][189][190], EBV [191]); cancer (colorectal cancer [192][193][194], NCLC [195], hepatocellular carcinoma [175,196], hematologic malignancies [197], pancreatic tumors [198], gastric cancer [199], breast cancer [200], thyroid cancer [201], melanoma [202], and lymphoma [203]); bacterial infection (Escherichia coli, Acinetobacter baumannii, Klebsiella pneumonia, Pseudomonas aeruginosa, and Staphylococcus aureus [204]); parasitic infection (Leishmania mexicana [205]); immunodeficiency disease (CVID <...…”
Section: Cxcr5 + Cd8 + T Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…6 Over the past decade, CXCR5 + CD8 + T cells have attracted increasing attention due to their unique ability to provide assistance to B cells in germinal centres and to maintain cytolytic capabilities similar to those of effector CD8 + T cells in infection, autoimmune and tumour microenvironments. [7][8][9] A recent study has shown that CXCR5 + CD8 + T cells produce HBV-specific cytokines and are dramatically associated with HBsAg and HBV-DNA reduction. More importantly, these cells commendably stimulate the activation of B-cells to assist in viral clearance and have the potential to be an efficacious therapeutic target for CHB.…”
mentioning
confidence: 99%